First principle integrated modeling of multi-channel transport including Tungsten in JET. (3rd July 2018) - Breton, S.; Casson, F.J.; Bourdelle, C.; Citrin, J.; Baranov, Y.; Camenen, Y.; Challis, C.; Corrigan, G.; Garcia, J.; Garzotti, L.; Henderson, S.; Koechl, F.; et al.
Abstract: For the first time, over five confinement times, the self-consistent flux driven time evolution of heat, momentum transport and particle fluxes of electrons and multiple ions including Tungsten (W) is modeled within the integrated modeling platform JETTO (Romanelli et al 2014 Plasma Fusion Res .9 1–4), using first principle-based codes: namely, QuaLiKiz (Bourdelle et al 2016 Plasma Phys. Control. Fusion 58 014036) for turbulent transport and NEO (Belli and Candy 2008 Plasma Phys. Control. Fusion 50 95010) for neoclassical transport. For a JET-ILW pulse, the evolution of measured temperatures, rotation and density profiles are successfully predicted and the observed W central core accumulation is obtained. The poloidal asymmetries of the W density modifying its neoclassical and turbulent transport are accounted for. Actuators of the W core accumulation are studied: removing the central particle source annihilates the central W accumulation whereas the suppression of the torque reduces significantly the W central accumulation. Finally, the presence of W slightly reduces main ion heat turbulent transport through complex nonlinear interplays involving radiation, effective charge impact on ITG and collisionality.